If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18(c + -1) = 0 Reorder the terms: -18(-1 + c) = 0 (-1 * -18 + c * -18) = 0 (18 + -18c) = 0 Solving 18 + -18c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -18c = 0 + -18 Combine like terms: 18 + -18 = 0 0 + -18c = 0 + -18 -18c = 0 + -18 Combine like terms: 0 + -18 = -18 -18c = -18 Divide each side by '-18'. c = 1 Simplifying c = 1
| 3x^2-8x=-4 | | 12z^2=7z^2+20 | | 4x^4=32x | | 5(r+9)-5r+9= | | 3x^2+24x+45=0 | | -3-4X=41 | | -2(x-9)-30=-12 | | 6x+15=5x+15 | | -5+5x-4-2x+3x= | | 8x^2-72=0 | | 88=3x+19 | | 3.7X+8=1.7X+16 | | 6x-5-4x=41 | | 4(0)+5y=-6 | | (4s-3)(5s-5)= | | 1.025+2.458=3.86 | | 18-2x=13x | | -1+14x=12x+17 | | 9x+(-14y)+(-15x)+10y= | | -2z^2+5z-1=0 | | 3x^2+60=0 | | 21-8(y+2)+3+7x= | | -2x+8=20 | | -6y+2=-4(2y+0) | | -7x=9+2x | | 2y-1=y-5 | | (0.16)(5x+3)=7x | | 9x=35+2x | | -2(p-5)+7=-5 | | 6(8x-7)=18x | | 0.11p+1.5=2.49n | | 8x=21+5 |